Um olhar para a despedida: um estudo do luto antecipatório e sua implicação no luto pós-morte - Rodriguez, Maria Inês Fernandez (2014)
The literature shows that family and patient (care facility) to receive a diagnosis of a disease that threatens the continuity of life, require actions for the prevention and relief of suffering, a look at the care unit, carefully for the current and prior to diagnosis , difficulties , problems in communication that contribute to conflict , factors that put stress on each stage of the disease process and the farewell relationship. Palliative care has actions that are based on management communication and emotions, a humanized care that integrates the advances of medical science for the physical well-being with interventions that are based on respect for individuality through listening, support and consider the process of anticipatory grief (RANDO, 2000), as an adaptive mechanism to promote opportunities for family and intimate, coping resources for protection in relation to complicated grief after death. Because it is an area of knowledge and practice that presents constant advances and reflections, we must delineate steadily emerging issues and their consequences. Here we present the aim of this work, using qualitative research to understand people's experiences and the subjective aspects of their experiences, aims to study the process of grieving adults in the family from the experience of anticipatory grief in a palliative care unit. Emphasis was placed on identifying aspects of anticipatory grief that can serve as a protective factor for development of post - death grief in different family members. For this goal to be achieved by two interviews open threads, allowing explore the issues and is essentially exploratory and flexible with each participant, the mother and sister of one patient who was treated in palliative care unit were performed. The results of these interviews indicate that interventions with this family were limited only to the proximity of death not taking into account other issues such as the representation of the patient in relation to the family and to each of its members, and to this day the participants a factor of risk for complicated grief. This study suggests that there is a need to extend the concepts of palliative care , as well as anticipatory grief, which consider important interventions aimed not only the proximity of death, but also diagnosis and disease process for a more complete approach with this population